QUANTUM DOTS APPLIED IN HEALTHCARE – CBEB 2024 - Araujo Vieira, M. V.; Pereira, G. S.; Garbim, F. M.; Araujo-Moreira, F. M. (Seven Editora, 2025)
This article addresses the applications of quantum dots in the health area, focusing on the applications of graphene and carbon dots. It also presents the explanation of what quan- tum dots are, and the motivation for using this technology in health. For this approach, research was carried out with several authors, in order to present to the reader the importance of fur- ther studies of this nanotechnology so that in the future it can be applied in the health network. It should be noted that only a portion of the studies already published on quantum dots and the health area have been addressed. DOI: https://doi.org/10.56238/sevened2024.037-152